2003
DOI: 10.1023/a:1022846304826
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Bmax, maximum binding capacity; BMCC, bacterial microcrystalline cellulose; CBH, cellobiohydrolase; CBM, carbohydrate-binding module; CBM-FITC, carbohydrate-binding module labelled with fluorescein isothiocyanate; CBM1, carbohydrate-binding module of family 1; FITC, fluorescein isothiocyanate; KD, dissociation constant; RP-HPLC, reversed phase HPLC; S1-S3, Secondary cell wall layers 1-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…Previous studies have shown that the binding of recombinant Histagged CBMs, at a concentration range of 1-5 g/ml, to plant cell walls can be detected using an indirect triple labeling immunofluorescence procedure (His-tagged CBM, anti-His mouse-Ig, anti-mouse Ig fluorescein isothiocyanate) (27,28). An initial study of CBM binding to transverse sections of a tobacco stem internode (sixth internode from the apex of a 6-week-old tobacco plant) indicated that type A CBMs from families 1, 2a, 3a, and 10, which recognize crystalline cellulose, bound more effectively to cell walls than type B CBMs from families 4-1, 17, and 28, which interact with internal regions of discrete ␤-glucan chains, and the type C CBM from family 9-2, which recognizes the reducing ends of polysaccharides (Fig.…”
Section: Type a Cellulose-directed Cbms Bind More Effectively To Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the binding of recombinant Histagged CBMs, at a concentration range of 1-5 g/ml, to plant cell walls can be detected using an indirect triple labeling immunofluorescence procedure (His-tagged CBM, anti-His mouse-Ig, anti-mouse Ig fluorescein isothiocyanate) (27,28). An initial study of CBM binding to transverse sections of a tobacco stem internode (sixth internode from the apex of a 6-week-old tobacco plant) indicated that type A CBMs from families 1, 2a, 3a, and 10, which recognize crystalline cellulose, bound more effectively to cell walls than type B CBMs from families 4-1, 17, and 28, which interact with internal regions of discrete ␤-glucan chains, and the type C CBM from family 9-2, which recognizes the reducing ends of polysaccharides (Fig.…”
Section: Type a Cellulose-directed Cbms Bind More Effectively To Cellmentioning
confidence: 99%
“…The recognition of cellulose in the context of cell walls by diverse families and types of CBM has not been systematically examined. It has been previously demonstrated that CBMs directly coupled to fluorophores or with His tag appendages can be used to investigate the localization of these proteins when bound to target polymers in the context of cell wall composites (27)(28)(29). Here, an immunofluorescence approach is used to interrogate the recognition by type A, B, and C cellulose-directed CBMs (Table 1) of polysaccharides in the context of primary and secondary cell walls in a range of species.…”
mentioning
confidence: 99%
“…This might perhaps partly explain the different results obtained. Other non-CLSM fluorescence microscopy studies showing enzymes binding to dislocations involved CBMs that were not used in our study (CBM3 and CBM28 of Clostridium josui on Japan cedar wood (Kawakubo et al 2010 ), CBM6 of Clostridium thermocellum on Valonia ventricusa cellulose (Ding et al 2006 ), CBM1 from Phanerochaete chrysoporum Cel7D on delignified spruce/birch pulp fibers [Hildén et al 2003 ]). Recently, swollenin has also been shown, by use of CLSM combined with other techniques, to target and disrupt dislocations (Gourlay et al 2015 ).…”
Section: Discussionmentioning
confidence: 86%
“…The use of CLSM differs from traditional binding studies (e.g. Filonova et al 2007 ; Hildén et al 2003 ) where the amount of bound enzyme is estimated based on what is present in the supernatant after a certain incubation period, giving no information on the location of the bound enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…5) Recently, such labeled CBMs have been used as molecular probes to study the architecture of plant cell walls. [5][6][7][8] The endoglucanase Cel5A from Clostridium josui contains a family 17 CBM (CjCBM17) and a family 28 CBM (CjCBM28) in tandem. 9) Both family 17 and family 28 CBMs from C. josui are type B CBMs.…”
mentioning
confidence: 99%